PAMSWAKARSA DALAM KONFLIK AGRARIA DI LAMPUNG: ANTARA KEPENTINGAN PERUSAHAAN, NEGARA, DAN MASYARAKAT - Gita Karisma (Inovasi Pembangunan : Jurnal Kelitbangan, 2021)
This research aims to explore pamswakarsa which was created by corporation and its position on on agrarian conflict in Lampung Province, Indonesia. By using qualitative approach through the methods of interviews and utilizing several related documents, this research finds that pamswakarsa is assumed as paramilitary. Pamswakarsa itself emerged while conflict is existing. It is not relavant enough to support the effort in achieving order and peaceful, as was legally mandated by the regulation from The Indonesian National Police through government regulation Number 43 the Year of 2012. Pamswakarsa tends to be involved in conflict and even has been the new actor/perpretrator against society. Keywords: conflict, corporation, Lampung, pam swakarsa, paramilitary, violent.